Effects of Isometric and Isotonic Training on work related musculoskeletal disorders among rubber tappers residing in kanyakumari District. - Mrs. Anbumalar,; Dr. Shanthi, PhD,; Dr. Arzta Sophiya, (The Bioscan, 2024)
Background Isometric and isotonic exercises are important modes of resistance training for enhancement of athletic performance. However, less is known about their effects on fitness and health in recreationally physically active individuals. Musculoskeletal disorders (MSD) are injuries or dysfunctions affecting muscles, bones, nerves, tendons, ligaments, joints, cartilages and spinal discs. MSD include sprains, strains, tears and connective tissue injuries, several interventions are proposed to reduce work-related MSD rates, including work adjustments, re-engineering type modifications, and training in ergonomic principles, exercise pro- grams and smoking cessation campaigns. There is some evidence for Isometric and Isotonic Training in reducing work-related MSD. Method: A total of 60 participants, all rubber tappers residing in kanyakumari District, with an average age of 30 - 50 years, were divided into control, experimental groups. Eight weeks of isometric and isotonic exercises were recommended to the participants The control group received no specific exercise program. Pre-test and post-test included the use of Stork balance test (SBT) and Pain Scale to assess the static, dynamic balance and pain level respectively. Results: After eight weeks of performing separate isometric and isotonic exercises on the lower and upper limbs, and according to the results of the pre-test and posttest a significant Decrease in leg pain level was observed (P < 0.05) and reduction in pain level Conclusion: isometric and isotonic exercises of lower limbs and upper Limbs showed a significant effect on the increased balance and pain Reduction Recommended exercises can be suggested according to the type of exercises as a factor for increasing static and dynamic balance.